Chemical Bond Based E-Worksheet Design Problem Based Learning With Approaches Differentiation To Improve Learning Outcomes Student - Devi, Carissa Salma; Haryani, Sri (Universitas Negeri Semarang, 2025)
This study aims to develop and evaluate a Chemistry Bonding e-worksheet based on Problem-Based Learning (PBL) with a differentiation approach to improve student learning outcomes at SMA Negeri 1 Ungaran. Using the 4D development model, which is limited to the Define, Design, and Develop stages, the e-worksheet is designed to meet students' needs based on literature studies and observations. This e-worksheet follows the PBL syntax, consisting of five stages, and is equipped with practice questions and a practical guide to support active learning and critical thinking skills. Validation results from subject matter and media experts indicate a high level of agreement, with a Cohen’s Kappa value of 0.853, categorized as very good. The N-Gain analysis indicates that the improvement in students' learning outcomes falls into the high category, with an overall score of 0.848. These findings suggest that the PBL-based e-worksheet with a differentiation approach is effective in enhancing student learning outcomes